Cultural Content Analysis of Elt Textbook for Firstyear Students in Senior High School - Maulia, Ismira; Puspitaloka, Nina; Utami, Praditya Putri (Jurnal Ilmiah Wahana Pendidikan, 2025)
Recognizing the significance of cultural content in language learning materials, this research undertakes a systematic analysis to evaluate the representation in the textbook Esensi Bahasa Inggris. Using qualitative content analysis method, this research dives into the cultural themes, topics, and perspectives presented in the Esensi Bahasa Inggris textbooks. However, the findings intended to understand how well ELT textbooks accommodate the diverse cultural backgrounds and identities of students, providing valuable insights for improving the cultural relevance and usefulness of language teaching materials in senior high school classrooms. The data sheet adopted from Cortazzi (1999) & Byram (1993) was used for the instrumentation. The result show cultural content with the highest frequency is Source Culture with 57% Then, it followed by International Culture which has 28%. And Target Culture shows that only 15% in total. However, the target culture also play an important to make students get used to recognising the English in its original form.